MOCCA-Survey Database I: Unravelling black hole subsystems in globular clusters - Arca Sedda, Manuel; Askar, Abbas; Giersz, Mirek (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. In this paper, we discuss how the structural and observational properties of globular clusters (GCs) can be used to infer the presence of a black hol
Gesehen am 11.02.2019